Makna Religi Tradisi Nyadran dan Atraksi Pencak Silat di Desa Abar abir - Khilmiyyah, Dahliyatul; Setyawan, Bagus Wahyu (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2023)
A tradition can be understood as a custom passed down through generations and still practised within a community. The most fundamental aspect of a tradition is the transmission of information from one generation to the next, whether written or oral, because, without this, a tradition will become extinct and will not evolve. There are many different traditions passed down in each region, such as in the village of Abar Abir in Gresik Regency, where the Nyadran and Pencak Silat traditions are practised. These traditions, handed down through generations, carry significant religious meanings and ancestral legacies, ensuring that future generations can continue them.